Capitalism against the planet: Posthuman ecocriticism in Alistair Mackay's It Doesn't Have To Be This Way. - Dobrogoszcz, Tomasz (Tydskrif vir Letterkunde, 2025)
In this article, I examine various dimensions of displacement resulting from the environmental crisis envisaged in the speculative debut novel of the South African author Alistair Mackay: It Doesn't Have To Be This Way (2022). The theoretical framework is located in the area of posthumanist studies but also involves elements of trauma theory, as the issue of psychological displacement is viewed through E. Ann Kaplan's concept of pretrauma, a paralysing anxiety about the future disaster evoked by the scenarios of the near apocalypse. I also offer a brief review of the political and economic conditions of post-apartheid South Africa, discussing the country's adoption of neoliberal tenets. Since Mackay's novel represents climate change as the result of ecologically hazardous activities of multinational corporations which stem from their colonial/imperialist commodification of the natural environment, my analysis draws from ecocritical African studies and contemporary critiques of capitalism, thus situating the climatic catastrophe of the Anthropocene in the context of destructive practices of the neoliberalist economy. Furthermore, in this article, I employ the posthumanist perspective (Hayles; Braidotti) to discuss the issue of body augmentation, presenting the reservations of Mackay's characters towards dehumanising effects of integrating our bodies with ultramodern technologies. Finally, a pro-active ecological endeavour of tree-planting is examined in the context of Donna Haraway's notion of the Chthulucene as well as a long-standing African appreciation of the forest--as a biological asset, regulating climate and farming, and as a spiritual one, the abode of deities.